A high accuracy voltage reference generator. (May 2018) - Souliotis, George; Plessas, Fotis; Vlassis, Spyridon
Abstract: A high-accuracy voltage reference generator is proposed in this paper. It has been designed in a CMOS 65 nm technology node, operating with a typical supply voltage of 1.2 V, which provides a reference voltage equal to 0.5 V. Measurement results of the fabricated chip show a reference voltage variation less than 0.04% over temperature range from −40 to 125 °C and less than 0.9% over temperature and supply voltage corners. The proposed design demonstrates a low noise output and good performance under mismatch. A current reference generator has been included in the design to provide a constant reference current. The measured variation of the reference current is about 1%.